Why are ELEvoHI CME Arrival Predictions Different if Based on STEREO‐A or STEREO‐B Heliospheric Imager Observations? - Jürgen Hinterreiter; Tanja Amerstorfer; Martin A. Reiss; Christian Möstl; Manuela Temmer; Maike Bauer; Ute V. Amerstorfer; Rachel L. Bailey; Andreas J. Weiss; Jackie A. Davies; Luke A. Barnard; Mathew J. Owens (Space Weather)
Abstract Accurate forecasting of the arrival time and arrival speed of coronal mass ejections (CMEs) is an unsolved problem in space weather research. In this study, a comparison of the predicted arrival times and speeds for each CME based, independently, on the inputs from the two STEREO vantage points is carried out. We perform hindcasts using ELlipse Evolution model based on Heliospheric Imager observations (ELEvoHI) ensemble modeling. An estimate of the ambient solar wind conditions is obtained by the Wang‐Sheeley‐Arge/Heliospheric Upwind eXtrapolation (WSA/HUX) model combination that serves as input to ELEvoHI. We carefully select 12 CMEs between February 2010 and July 2012 that show clear signatures in both STEREO‐A and STEREO‐B HI time‐elongation maps, that propagate close to the ecliptic plane, and that have corresponding in situ signatures at Earth. We find a mean arrival time difference of 6.5 h between predictions from the two different viewpoints, which can reach up to 9.5 h for individual CMEs, while the mean arrival speed difference is 63 km s−1. An ambient solar wind with a large speed variance leads to larger differences in the STEREO‐A and STEREO‐B CME arrival time predictions (cc = 0.92). Additionally, we compare the predicted arrivals, from both spacecraft, to the actual in situ arrivals at Earth and find a mean absolute error of 7.5 ± 9.5 h for the arrival time and 87 ± 111 km s−1 for the arrival speed. There is no tendency for one spacecraft to provide more accurate arrival predictions than the other.